Public Interest in Islamic Equity Crowdfunding - Trifiyanto, Kabul (Institut Agama Islam Negeri Kendari, 2023)
Equity Crowdfunding is an alternative investment instrument. Indonesia, with the largest Muslim population, is a potential market for Islamic Equity Crowdfunding. The purpose of this study is to identify the motivation of investors to invest in this instrument. There are three subject sizes, namely, related to project funding (network externality and perceived informativeness), related to a platform (perceived accreditation, structural assurance, and third-party seal) related to fundraising (Islamic value congruence, social interaction ties). Belief perspective is divided into cognitive and affective. The sample used is 101 investors spread across Indonesia in a national equity crowdfunding company with Islamic-based management. The data was processed using the structural equation modeling technique using the WarpPLS 7.0 tool. The results of this study prove that cognitive and affective beliefs and network externalities directly influence investor interest. Trust is proven to be able to mediate perceived informativeness on interest. The form of investor cognitive trust is perceived accreditation and third-party seal. The shapers of an investor's affective trust are perceived informativeness, structural assurance, and Islamic value congruence. This finding can be used as the basis for how startup companies in Sharia-based equity crowdfunding instruments build trust and interest.